Type 1 diabetes mellitus in children: Patient reported outcomes - Basima A. Almomani; Roa’a N. Elayyan; Samah F. Al-Shatnawi (PLoS ONE, 2025)
The global prevalence of type 1 diabetes mellitus (T1DM) is increasing. Poor glycemic control in children and adolescents leads to both acute and chronic problems, reduced Health Related Quality of Life (HRQoL), and higher healthcare utilization. This study aimed to assess patient-reported outcomes related to self-management adherence, QoL, diabetes-related stigma, glycemic control, and other clinical outcomes along with their determinants, in insulin-treated pediatric T1DM patients in Jordan. A cross-sectional study was conducted from April to October 2023 at two health centers in Northern Jordan. Eligible pediatric T1DM patients attending outpatient clinics were enrolled. Trained pharmacists conducted face-to-face interviews with both children and their guardians, using validated tools that were translated into Arabic. Adherence was evaluated using the Diabetes Management Questionnaire, HRQoL was measured using the Pediatric Quality of Life Inventory 3.0 Diabetes Module, stigma was assessed using the Child Attitude Toward Illness Scale and glycemic control was determined by glycated hemoglobin levels. A total of 150 patients participated in the study. The mean adherence score was 57.4 ± 18.13. Factors such as younger age (P-value = 0.01), higher monthly income (P-value = 0.022) and shorter disease duration (P-value = 0.008) were associated with improved adherence. The mean pediatric QoL score was 63.27 ± 11.86, with male gender (P-value = 0.021) and the absence of disease-related factors (P-value = 0.004) linked to lower QoL scores. Additionally, body mass index (P-value = 0.041) and a family history of DM (P-value = 0.047) were linked to stigma. Most patients (76%) had uncontrolled diabetes, with disease duration (P-value = 0.019) and maternal educational level (P-value = 0.013) influencing glycemic control. These findings highlight that, despite widespread poor glycemic control, insulin adherence and QoL among pediatric T1DM patients in Jordan are above average. Targeted interventions are recommended to improve adherence and, in turn, overall patient outcomes.